Pengaruh Perbedaan Bagian Daging Ayam Broiler terhadap Kandungan Protein dan Sifat Organoleptik Nugget Ayam: Effect of Differences in Broiler Chicken Meat Parts on Protein Content and Organoleptic Properties of Chicken Nuggets - Afiyah, Dyah Nurul (Anoa: Journal of Animal Husbandry, 2022)
Chicken nuggets are a processed chicken meat product that is ground, added spices, then given flour that functions as an adhesive so that a dough is formed that blends with the meat, then greased the outside with eggs and breadcrumbs. The purpose of the study was to determine the protein content and organoleptic quality of chicken nuggets processed from different parts of broiler chicken meat. The research used a Complete Randomized Design (RAL), the research treatment consisted of 4 treatments and 7 repetitions, P1: Chest, P2: Upper Thigh, P3: Lower Thigh and P4: Wing. The research variables observed in nuggets consist of protein content using the Kjeldahl method and organoleptic tests. Organoleptic tests include color, aroma, taste, texture and preferences. The results of the study, it can be concluded that color and aroma show very significant different. For the taste and chewiness variables show significant different. For the favorability and protein variables, the results are not significantly different. The best research results were obtained at P1 with a protein content result of 19.43%. color by 3.53%, taste by 3.43%, aroma by 3.07%, chewiness by 2.44%, favorability by 2.91%.